ISOLASI DAN UJI AKTIVITAS ENZIM SELULASE PADA BAKTERI SELULOLITIK DARI SERASAH AKASIA (Acacia mangium Willd.) - Tazkiatun Nufus; Diannita Harahap (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
Cellulase is an enzyme with high demand in the industrial sector and can be extracted from cellulolytic bacteria. These bacteria are capable of producing cellulase and hydrolyzing cellulose into simple products such as glucose. The content of acacia leaves consists of 50.77% cellulose, hemicellulose, and lignin. This study aimed to determine the characteristics, identification, and enzymatic activity of cellulolytic bacteria isolated from acacia litter (Acacia mangium Willd.). The methods used in this research were both quantitative and qualitative, involving the isolation of cellulolytic bacteria from acacia litter using selective CMC media by the spread plate method, clear zone testing using the Kirby–Bauer method, and enzyme activity assays. Eight cellulolytic bacterial isolates (BS1, BS2, BS3, BS4, BS5, BS6, BS7, and BS8) with different morphological characteristics were obtained. Based on macroscopic, microscopic, and biochemical identification, the isolates were identified as belonging to the genera Cellulomonas sp. (BS1 and BS3), Pseudomonas sp. (BS2, BS4, BS5, BS6, and BS8), and Corynebacterium sp. (BS7). The two isolates showing the highest clear zone indices on CMC media were BS1 with an IS value of 0.90 and BS7 with an IS value of 0.74. The cellulase enzyme activity of isolate BS1 (Cellulomonas sp.1) was 0.0041 U/mL with a specific activity of 0.0032 U/mL, while that of isolate BS7 (Corynebacterium sp.) was 0.0049 U/mL with a specific activity of 0.0019 U/mL. Keywords: cellulase enzyme; cellulolytic bacteria; Acacia mangium Willd.